Geographic Concentration of Business Services Firms: A Poisson Sorting Model - Hans Koster; Jos van Ommeren; Piet Rietveld (European Regional Science Association (ERSA), 2011)
This paper estimates a heterogeneous sorting model for firms, employing a semiparametric Poisson approach. We show that there is an equivalence relation between a locally weighted Logit and Poisson model. We apply our model to estimate firm-specific preferences of business services firms for location attributes such as diversity of economic activities and specialisation of business services. We correct for endogeneity of our specialisation measure by means of a control function approach, using instruments external as well as internal to the model. We find that business services firms have a relatively strong preference for specialised clusters of business services firms, conditional on density of economic activity. A standard deviation increase in business services specialisation of a location leads to a 40 percent increase in the probability that a business services firm locates there, supporting theories of Marshall, Arrow and Romer. Business services firms also have a preference to locate near a group of firms that belong to the same sector, not necessarily business services firms, so diversity is negatively related to location decisions. Interestingly, firms rely either on within-sector interactions (specialisation) or between-sector interactions (diversity).
Keywords: 330